The Influence of a Bifidobacterium animalis Probiotic on Gingival Health: A Randomized Controlled Clinical Trial - KURU, LEYLA (AMER ACAD PERIODONTOLOGY, 2017)
Background: There is growing interest in the use of probiotics in periodontal therapy; however, until now, most research has focused on lactobacilli probiotics. The aim of this study is to evaluate the effect of 4-week use of yogurt supplemented with Bifidobacterium animalis subsp. lactis DN-173010 versus a placebo yogurt, followed by a 5-day non-brushing period. Methods: Individuals were included in this single-mask, randomized, controlled study if probing depth (PD) was <= 3 mm and attachment loss was <= 2 mm. After professional prophylaxis, they were randomized into two groups receiving yogurt containing either placebo or B. animalis for 28 days, followed by a 5-day non-brushing period. Outcome measures were plaque index (PI), gingival index (GI), bleeding on probing (BOP), PD, gingival crevicular fluid (GCF) volume, and total amount and concentration of interleukin (IL)-1 beta in GCF. These were measured at baseline, after 28 days of study product use, and subsequently after 5 days of plaque accumulation. Results: Fifty-one patients were analyzed. No intergroup differences could be detected before and after intake of study products. However, after plaque accumulation, significantly better results for all parameters were seen in the probiotic group compared with the control group (P < 0.001): lower PI and GI, less BOP, less increase in GCF volume, and lower IL-1 beta total amount/concentration. Conclusion: The use of a probiotic yogurt supplemented with B. animalis can have a positive effect on plaque accumulation and gingival inflammatory parameters after refraining from oral hygiene practices.
Keywords: Bifidobacterium; Bifidobacterium animalis; gingivitis; probiotics; yogurt; SALIVARY MUTANS STREPTOCOCCI; LACTOBACILLUS-RHAMNOSUS GG; PLAQUE-INDUCED GINGIVITIS; PERIODONTAL-DISEASE; CREVICULAR FLUID; ICE-CREAM; LACTIS BB-12; IN-VITRO; REUTERI; INFLAMMATION